A comparison between six-step and sine-wave commutation methods for brushless direct current motors - Hilmi Yafi Al-Faruq; Harry Septanto (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This research is focused on the design and implementation of an electronic circuit for commuting a brushless direct current (BLDC) motor and its data acquisition system, as well as conducting experiments on them. We propose a drive circuit using two modules, each consist of a dual H-bridge, that are cheap and can be easily obtained. Two different commutation methods, namely six-step and sine-wave commutations, are applied. Each of these implements a different way for its open-loop speed control, i.e., a voltage-controlled-current-source is implemented along with the six-step commutation and the step duration approach is implemented along with the sine-wave commutation. The experiment data are acquired using a developed desktop application. Some experiment results lead us to find that, on its own, both commutation methods have a narrow range of speed. Nevertheless, if both methods are used together, this range can be increased. Also, the relation between speed and its controlling signals for both methods are shown.